The Wiskott-Aldrich Syndrome Protein Contributes to the Assembly of the LFA-1 Nanocluster Belt at the Lytic Synapse - Raïssa Houmadi; Delphine Guipouy; Javier Rey-Barroso; Zilton Vasconcelos; Julie Cornet; Manoel Manghi; Nicolas Destainville; Salvatore Valitutti; Sophie Allart; Loïc Dupré (Cell Reports, 2018)
T lymphocyte cytotoxicity relies on a synaptic ring of lymphocyte function-associated antigen 1 (LFA-1), which permits polarized delivery of lytic granules. How LFA-1 organization is controlled by underlying actin cytoskeleton dynamics is poorly understood. Here, we explored the contribution of the actin cytoskeleton regulator WASP to the topography of LFA-1 using a combination of microscopy modalities. We uncover that the reduced cytotoxicity of Wiskott-Aldrich syndrome patient-derived CD8+ T lymphocytes lacking WASP is associated with reduced LFA-1 activation, unstable synapse, and delayed lethal hit. At the nanometric scale, WASP constrains high-affinity LFA-1 into dense nanoclusters located in actin meshwork interstices. At the cellular scale, WASP is required for the assembly of a radial belt composed of hundreds of LFA-1 nanoclusters and for lytic granule docking within this belt. Our study unravels the nanoscale topography of LFA-1 at the lytic synapse and identifies WASP as a molecule controlling individual LFA-1 cluster density and LFA-1 nanocluster belt integrity.